Peran guru Pendidikan Agama Islam dalam membentuk akhlakul karimah peserta didik - Manjalani, Masasi; Alfaein, Noor Isna (Idarah Tarbawiyah: Journal of Management in Islamic Education, 2025)
This study discusses the role of Islamic religious education teachers in forming good morals for their students. The author's observations at SMKS Ibnu Sobri Jonggol, there is still a lack of teacher roles in carrying out their duties, so that they become bad examples for students, such as being late and often absent from teaching. The purpose of this study is to determine the role of Islamic religious education teachers in forming good morals for students and the supporting and inhibiting factors for the development of the school. This study uses a qualitative approach using the case study method. The results of this study are that the role of Islamic religious education teachers has not been able to create good morals for students without assistance from other teachers. This study emphasizes that the role of Islamic religious education teachers is indeed important, but their role has not been able to form good morals for students due to the lack of collaboration and assistance from other teachers. So that students lack attention, guidance and supervision. The lack of teaching staff and facilities is part of the inhibiting factors for school development. Abstrak Penelitian ini membahas peran guru pendidikan agama Islam dalam membentuk akhlakul karimah bagi peserta didiknya. Observasi penulis pada SMKS Ibnu Sobri Jonggol, masih terlihat kurangnya peran guru dalam menjalankan tugasnya, sehingga menjadi contoh tidak baik bagi peserta didik, seperti keterlambatan dan sering tidak masuk mengajar. Tujuan penelitian ini ialah untuk mengetahui bagaimana peran guru pendidikan agama Islam dalam membentuk akhlakul karimah peserta didik dan adanya faktor pendukung serta penghambat perkembangan sekolah tersebut. Penelitian ini menggunakan pendekatan kualitatif dengan menggunakan metode studi kasus. Hasil penelitian ini adalah bahwa peran guru PAI belum mampu membuat akhlak baik terhadap peserta didik tanpa adanya bantuan dari guru-guru lain. Dalam penelitian ini menegaskan bahwa peran guru PAI memang penting, namun peranannya belum mampu membentuk akhlak peserta didik karena kurangnya kolaborasi dan bantuan dari guru-guru lainnya. Sehingga membuat peserta didik kurang dalam perhatian, bimbingan dan pengawasan. Kekurangan tenaga pendidik dan fasilitas menjadi bagian dari faktor penghambat perkembangan sekolah.